Cerebral Blood Flow Pattern Changes in Unilateral Sudden Sensorineural Hearing Loss - Chen, Yue; Li, Haimei; Liu, Bing; Gao, Wenwen; Yang, Aocai; Lv, Kuan; Xia, Hui; Zhang, Wenwei; Yu, Hongwei; Liu, Jian; Liu, Xiuxiu; Wang, Yige; et al. (Frontiers in Neuroscience, 2022)
Objective: This study analysed the differences in the cerebral blood flow (CBF) between unilateral Sudden Sensorineural Hearing Loss (SSNHL) patients and healthy controls (HCs). We also investigated CBF differences in auditory-related areas in patients with left- and right-sided SSNHL (lSSNHL and rSSNHL) and HCs. We further explore the correlation between unilateral SSNHL characteristics and changes in the CBF. Methods: 36 patients with unilateral SSNHL (15 males and 21 females, 40.39±13.42 years) and 36 HCs (15 males and 21 females, 40.39±14.11 years) were recruited. CBF images were collected and analyzed using arterial spin labeling (ASL). CereFlow software was used for the post-processing of the ASL data to obtain the CBF value of 246 subregions within brainnetome atlas (BNA). The Two-sample t-test was used to compare CBF differences between SSNHL patients and HCs. One-way ANOVA or Kruskal-Wallis test was used to compare the CBF difference of auditory-related areas among the three groups (lSSNHL, rSSNHL and HCs). Then, the correlation between CBF changes and specific clinical characteristics were calculated. Results: The SSNHL patients exhibited decreased CBF in the bilateral middle frontal gyrus (MFG, MFG_7_1 and MFG_7_3), the contralateral precentral gyrus (PrG, PrG_6_3) and the bilateral superior parietal lobule (SPL, bilateral SPL_5_1, SPL_5_2 and ipsilateral SPL_5_4), p<0.0002. Compared with HCs, unilateral SSNHL patients exhibited increased rCBF in the bilateral orbital gyrus (OrG, OrG_6_5), the bilateral inferior temporal gyrus (ITG, contralateral ITG_7_1 and bilateral ITG_7_7), p<0.0002. lSSNHL showed abnormal CBF in left BA21 caudal (p=0.02) and left BA37 dorsolateral (p=0.047). We found that the CBF in ipsilateral MFG_7_1 of SSNHL patients was positively correlated with tinnitus Visual Analogue Scale (VAS) score (r＝0.485, p＝0.008). Conclusion: Our preliminary study explored CBF pattern changes in unilateral SSNHL patients in auditory-related areas and non-auditory areas, suggesting that there may exist reduced attention and some sensory compensation in patients with SSNHL. These findings could advance our understanding of the potential pathophysiology of unilateral SSNHL.